Socialization of Making Egg Shell Powder as a Water Purifying Material in Senoni Village, Sebulu District, Kutai Kartanegara Regency - Zarkasi, Ahmad; Ratnasari Putri, Erlinda; Nurhanafi, Kholish; Hamdani, Dadan; Perdana, Akbar; Nurohman, Ali; Munir, Rahmawati (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2023)
The production of eggshell powder as a water purifier has the potential to be utilized in Senoni Village, Sebulu District, Kutai Kartanegara Regency, East Kalimantan. Based on the results of initial observations the majority of residents there use Mahakam river water for daily needs where the water is still classified as cloudy. The purpose of implementing Community Service Activities is through socializing the production and utilization of eggshell powder as a water purifier and providing assistance through training activities on the powder as a water purifier. The approach method used were the lecture method, demonstration method, and mentoring method. Furthermore, the stages of socialization implementation as a solution to overcome the problems are as follows: 1) sample preparation stage, 2) socialization preparation stage, 3) implementation stage, and 4) evaluation stage. The results of the activity showed that an increase of 84% of participants knew the procedure for making eggshell flour, and 60% felt that it was very easy to make so it was very possible for participants to make it independently at their respective homes. This activity went well and smoothly without any significant problems. Participants are interested and want to implement the new knowledge that has been obtained through this socialization method, scientific findings results, and a short conclusion. The abstract should only be typed in one paragraph and one-column format.